Faktor Risiko Leiomyoma Uterus di Rumah Sakit Umum Pusat Dr. Kariadi Semarang - Prasetyo, Adi; Nuraini, Novita; Rachmawati, Ervina; Vestine, Veronika (Politeknik Negeri Jember, 2025)
Uterine leiomyoma is a benign tumor originating from the smooth muscle and fibrous tissue of the uterus, with a global prevalence of 60–75% among women of reproductive age. In 2023, 978 cases of uterine leiomyoma were recorded at Dr. Kariadi General Hospital, Semarang. The incidence of uterine leiomyoma has shown a continuous increase in morbidity and mortality rates over the years. This study aims to analyze the association between risk factors—age, obesity, parity, hormonal contraceptive use, and family history—and the occurrence of uterine leiomyoma. A case-control design was employed using secondary data, involving 70 cases and 70 controls selected through simple random sampling. Data analysis was conducted using univariate and bivariate methods with the chi-square test. The results revealed significant associations between uterine leiomyoma and age (p=0.029; OR=6.048), obesity (p=0.001; OR=3.579), and parity (p=0.037; OR=0.448). In contrast, hormonal contraceptive use (p=0.426) and family history (p=1.000) showed no association. It can be concluded that women aged 20–50 years, those with obesity, and multiparous or grand multiparous women are at higher risk of developing uterine leiomyoma. Strengthening health education and early detection among at-risk groups is recommended through health promotion, healthy dietary practices, and regular physical activity.